Enhancement of mobile-based teaching assessment using mobility mediation to facilitate self-determination theory and technology acceptance model - Abdirahman, Abdullahi Ahmed (2018)
The rapid growth of technology has ushered new applications which replace traditional methods. These include e-learning, e-health, etc. Mobile-Based Teaching Assessment (MBTA) has thus emerged as an alternative method for teaching assessment. The adoption of MBTA is driving by user’s acceptance to apply teaching assessment through technology. However, the objective of this research is to develop a model which explores the impact of mobility mediation to facilitate the theories of Self-Determination Theory and Technology Acceptance Model in the context of Mobile-Based Teaching Assessment. The study uses Partial Least Squares (PLS). The data were collected among members of the Universiti Putra Malaysia from One-hundred and forty students, lecturers and academic support using convenient sampling method. The results show that Perceived Mobility has a significant positive impact on the intention to use MBTA. The result suggested that 87% of the variation of user's intention to use MBTA is explained by the mobility mediation, while the evidence proved that TAM and SDT had pronounced the adoption of mobile-based teaching assessment (MBTA) in context of the academic arena. These findings highlight the significance of the proposed model.